Dinamika Regulasi Komunikasi Publik dalam Sistem Sosial: Perspektif Autopoiesis Luhmann - Rudy Chandra; Hasan Sazali (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This study aims to analyze the dynamics of public communication regulation in the social system from the perspective of Luhmann's autopoiesis. This study uses a qualitative method with a library research approach. The data of this study is sourced from relevant literature. Data analysis is carried out by reducing data, presenting data, and drawing conclusions. The validity of the data in this study was carried out through a credibility test. The results of this study show that in the dynamics of public communication regulation in the social system based on Luhmann's autopoiesis perspective, public communication regulation functions to maintain a balance between information disclosure, control, and system adaptability to rapid social change. Luhmann emphasized that public communication systems must continue to produce and reproduce elements that ensure their functions continue to function, such as transparency, trust, and responsiveness. Adaptive regulations allow the government to interact effectively with the public, especially in the digital era which presents challenges such as misinformation, disinformation, and rapid information flow. Cross-sector collaboration and regulatory flexibility are needed to maintain social stability and strengthen the relationship between the government and society, with information disclosure as a key pillar. However, the regulation must also include privacy protection and control over the spread of invalid information, so that public communication systems remain relevant, accountable, and able to adapt to evolving social dynamics.